KAJIAN PENGARUH PROGRAM NASIONAL UPAYA KHUSUS PENINGKATAN PRODUKSI PADI TERHADAP KEMISKINAN PERDESAAN DI WILAYAH BARAT DAN TIMUR INDONESIA - Krisnawati, Estifania; Suman, Agus; Saputra, Putu Mahardika A. (EP FEB UNS, 2018)
Increasing population in Indonesia spur increased demand for rice. On the other hand, national rice production as a rice-producing commodity is not optimal due to limited capital owned by farmers and the number of damaged irrigation infrastructures. This has an impact on the farmers' incomes that are less than optimal and the high poverty rate in rural areas requires public policy in the form of government expenditures, one of which is rolled out through the national program of Special Efforts (UPSUS) for Increasing Rice Production. This study aims to determine the effect of UPSUS funds directly or indirectly to rural poverty in the western and eastern regions of Indonesia. Using path analysis, the findings of the study indicate that the direct impact of the program on poverty is apparent in the eastern region with a positive coefficient. Meanwhile, the indirect effect of program funds on rural poverty through rice production and GDP of the food crops sub-sector shows positive values both in the west and east. As well as the indirect effect of program funds on poverty through rice production occurs only in the eastern region by showing negative coefficients.. Keywords: Government Expenditure, Rural Poverty, UPSUS PAJALEJEL Classification:H5, Q180